Systemic Induction of the Small Antibacterial Compound in the Leaf Exudate During Benzothiadiazole-elicited Systemic Acquired Resistance in Pepper - Boyoung Lee; Yong-Soon Park; Hwe-Su Yi; Choong-Min Ryu (The Plant Pathology Journal, 2013)
Plants protect themselves from diverse potential pathogens by induction of the immune systems such as systemic acquired resistance (SAR). Most bacterial plant pathogens thrive in the intercellular space (apoplast) of plant tissues and cause symptoms. The apoplastic leaf exudate (LE) is believed to contain nutrients to provide food resource for phytopathogenic bacteria to survive and to bring harmful phytocompounds to protect plants against bacterial pathogens. In this study, we employed the pepper-Xanthomonas axonopodis system to assess whether apoplastic fluid from LE in pepper affects the fitness of X. axonopodis during the induction of SAR. The LE was extracted from pepper leaves 7 days after soil drench-application of a chemical trigger, benzothiadiazole (BTH). Elicitation of plant immunity was confirmed by significant up-regulation of four genes, CaPR1, CaPR4, CaPR9, and CaCHI2, by BTH treatment. Bacterial fitness was evaluated by measuring growth rate during cultivation with LE from BTH- or water-treated leaves. LE from BTH-treatment significantly inhibited bacterial growth when compared to that from the water-treated control. The antibacterial activity of LE from BTH-treated samples was not affected by heating at 100°C for 30 min. Although the antibacterial molecules were not precisely identified, the data suggest that small (less than 5 kDa), heat-stable compound(s) that are present in BTH-induced LE directly attenuate bacterial growth during the elicitation of plant immunity.